Components of Story Comprehension and Strategies to Support Them in Hearing and Deaf or Hard of Hearing Readers. Issue 2 (April 2015) - Sullivan, Susan; Oakhill, Jane
<x xml:space="preserve">Abstract</x> In this article, we review the skills that have been found to be related to good story comprehension in novice readers with normal hearing and describe the relative weight each plays. The relationship between effective story comprehension and lower level skills (such as syntactic awareness and vocabulary knowledge) is considered, and the casual relations between discourse-level skills (such as inference abilities and story-structure understanding) and good text comprehension are delineated. We then compare this information with what is known about the abilities of children who are deaf or hard of hearing (DHH) and review the current research findings concerned with text intervention strategies designed for this population. Drawing on research with both hearing and DHH readers, we make suggestions for future text intervention strategies and research for DHH readers, which emphasize the need for research on practices that are directed (at least in part) at training the discourse-level component skills involved in effective story comprehension.